Parenting Patterns, Legal Protection and Socio-Economic Welfare for Abandoned Children in West Nusa Tenggara - Maemunah, Maemunah; Hafsah, Hafsah; Sakban, Abdul (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Child protection is the responsibility of the government and society. However, children's rights are still neglected. This research aims to explain parenting patterns, legal protection and socio-economic welfare for neglected children in West Nusa Tenggara. The type of research is qualitative, the approach is case studies and legislation. The research subjects were 9 informants. Data collection consists of observation, in-depth interviews and document analysis. Data analysis uses descriptive. The results of this research show that the pattern of care for neglected children is through communication, education and training approaches, and child caretakers in the orphanage act as the child's parents. Legal protection for abandoned children must be guided by legal principles, namely hierarchical protection of children's rights, law enforcement, legal assistance and the implementation of sanctions for neglect. The socio-economic welfare of neglected children focuses on their dignity, and social welfare and non-formal education to increase interests and talents. So care, protection and social welfare of children are ways to educate neglected children.